DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-UHPLC METHOD FOR THE ESTIMATION OF IMEGLIMIN HYDROCHLORIDE USED FOR THE TREATMENT OF METABOLIC DISORDER DIABETES MELLITUS - JAIN, AVNISH; SONI, LOVE KUMAR; SHARMA, RAJESH (International Journal of Applied Pharmaceutics, 2023)
Objective: The present work was aimed to develop and validate a novel, simple, rapid, consistent, and sensitive stability indicating reverse phase ultra-high-performance liquid chromatographic (RP-UHPLC) method for the determination of oral anti-diabetic drug Imeglimin Hydrochloride in bulk and pharmaceuticals dosage form as per the technical recommendations of International Council for Harmonization guidelines for human use pharmaceutical (ICH-Q2(R1)). Methods: A novel simple, selective, stable and sensitive stability indicating method which used isocratic RP-UHPLC methodology for the quantitative measurement of Imeglimin Hydrochloride was developed. The chromatographic separation of Imeglimin Hydrochloride was achieved on RP-UHPLC equipped with Hypersil gold ODS endcapped column of dimensions (150x4.6 mm, 3micron) using isocratic elution with a mobile phase consisting of water: acetonitrile in a ratio of (15:85% v/v) at a flow rate of 1 ml/min with an injection volume of 20 µl. All measurements are done on 240 nm using eight channels Dionex Ultimate 3000 PDA detector equipped with chromeleon data acquisition system for data integration. Validation of the proposed method was carried out according to the (ICH-Q2 (R1)) guidelines. Results: The retention time of the Imeglimin Hydrochloride was found to be 3.831 with excellent absorbance sensitivity at 240 nm wavelength. The linear regression equation was found to be y = 3199x+1605.5 with a correlation coefficient (R2)>0.999 which shows excellent linear correlation. Specificity, linearity, precision, accuracy robustness, LOD and LOQ were determined for method validation and results were found to be well within recommended limits as per ICH guidelines. Conclusion: The proposed stability indicating reverse phase ultra-high-performance liquid chromatographic (RP-UHPLC) method was found to be fast, affordable, robust, precise and specific for estimation of Imeglimin Hydrochloride in pharmaceutical dosage form.